U-net Based Autonomous Fetal Segmentation From 2D and 3D Ultrasound Images - Mithila, Maliha Tabassum; Prome, Tasnim Ahsan; Tabassum, Elmi; Kamrul, Sameha; samiha, Nausheen (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.